background image

14.3. CONSEQUENCES

250

Using the fact that every function induces a complete funcoid and a lemma

above we get:

FCD

f

A

=

l

FCD

f

Z

{

n

} ×

RLD

u

2

n

+1

n

Z

=

l

Z

{

n

} ×

RLD

u

2

n

n

Z

=

B

.

FCD

g

B

=

l

FCD

g

Z

{

n

} ×

RLD

u

2

n

n

Z

=

l

Z

{

n

1

} ×

RLD

u

2

n

1

n

Z

=

l

Z

{

n

} ×

RLD

u

2

n

+1

n

Z

=

A

.

It remains to show that

A

and

B

are not isomorphic.

Let

X

up(

Z

{

n

} ×

RLD

u

2

n

+1

) for some

n

Z

. Then if

Z

×

N

X

u A

is an

ultrafilter we have

Z

×

N

X

u A

=

Z

{

n

} ×

RLD

u

2

n

+1

and thus by the theorem

1322

is isomorphic to

u

2

n

+1

.

If

X /

up(

Z

{

n

} ×

RLD

u

2

n

+1

) for every

n

Z

then (

Z

×

N

)

\

X

up(

Z

{

n

} ×

RLD

u

2

n

+1

) and thus (

Z

×

N

)

\

X

up

A

and thus

Z

×

N

X

u A

=

Z

×

N

.

We have also

(

Z

{

0

} ×

RLD

N

)

u B

= (

Z

{

0

} ×

RLD

N

)

u

l

Z

{

n

} ×

RLD

u

2

n

n

Z

=

l

(

Z

{

0

} ×

RLD

N

)

u

(

Z

{

n

} ×

RLD

u

2

n

)

n

Z

=

Z

{

0

} ×

RLD

u

0

(an ultrafilter).

Thus every ultrafilter generated as intersecting

A

with a principal filter

Z

×

N

X

is isomorphic to some

u

2

n

+1

and thus is not isomorphic to

u

0

. By the lemma it

follows that

A

and

B

are non-isomorphic.

14.3.1. Metamonovalued reloids.

Proposition

1329

.

(

T

G

)

f

=

T

g

G

(

g

f

) for every function

f

and a set

G

of binary relations.

Proof.

(

x, z

)

\

G

f

y

: (

f x

=

y

(

y, z

)

\

G

)

(

f x, z

)

\

G

g

G

: (

f x, z

)

g

g

G

y

: (

f x

=

y

(

y, z

)

g

)

g

G

: (

x, z

)

g

f

(

x, z

)

\

g

G

(

g

f

)

.